Target Blood Pressure and Combination Therapy: Focus on Angiotensin Receptor Blockers Combination with Either Calcium Channel Blockers or Beta Blockers - Farag, Selvia M.; Rabea, Hoda M.; Abdelrahim, Mohamed E.; Mahmoud, Hesham B. (Current Hypertension Reviews, 2022)
Background: The target blood pressure has changed many times in the guidelines in past years. However, there is always a question; is it good to lower blood pressure below 120/80 or not? Control of blood pressure in hypertension is very important in reducing hypertension-modified organ damage. So, the guidelines recommend combining more than one antihypertensive drug to reach the target blood pressure goal. Results: Combination therapy is recommended by guidelines to reach the blood pressure goal. The guidelines recommend many combinations, such as the combination of angiotensin receptor blockers with either calcium channel blockers (CCB) or beta-blocker (BB). Angiotensin receptor blocker (ARB) combination with CCB has gained superiority over other antihypertension drug combinations because it reduces blood pressure and decreases the incidence of CV events and organ damage. BB combinations are recommended by guidelines in patients with ischemic events but not all hypertensive patients. Unfortunately, the new generation BB, for example, nebivolol, has a vasodilator effect, making it new hope for BB. Conclusion: Combination therapy is a must in treating the hypertensive patient. The new generation BBs may change the recommendations of guidelines because they have an effect that is similar to CCBs.